Method for depolymerizing polyurethane
Patent Information
- Application Number
- CN202380053620.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-14
- Filing Date
- 2023-07-13
- Publication Date
- 2025-03-14
Smart Images

Figure CN119630729A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of chemical recycling of polymers. More specifically, the present invention relates to a method for depolymerization of polyurethanes based on mild reaction conditions and using an active reaction medium which is stable over time and completely recyclable and reusable, thereby obtaining polyol substances which are easily separated from the reaction medium and can be used again in the synthesis of new polyurethanes without the need for subsequent purification steps. Background Art
[0002] Polyurethane is a polymer obtained by reacting a polyol with a diisocyanate. If the polymerization is carried out in the presence of a controlled amount of water, urethane (-NH-CO-O-) bonds and urea (-NH-CO-NH-) bonds are formed. With the help of FT-IR, the 1700-1740 cm -1 The band between the two selectively and unambiguously identifies the urethane bond [L. Zhao, V. Semetey. ACS Omega, 2021, 6, p. 4175-4183]. Based on their chemical structure, polyurethanes are divided into two major categories, which differ in their response to temperature: thermoplastics, which can melt and flow with temperature before degrading; and thermosetting plastics, which maintain their shape and strength under high pressure and high temperature conditions. The excellent properties of the latter class of materials, including polyurethane foams, make polyurethane one of the most widely used polymers for the manufacture of thermal insulation and consumables such as mattresses, seats, furniture or sponges for cleaning. In 2017, the production of this polymer was 22.9 million tons, and has since grown at an annual rate of 4.5%.
[0003] As a result of this growing demand, an estimated 10% of the total polyurethane production corresponds to removed post-production products and post-production waste, which are discarded or incinerated due to the lack of beneficial and easily implementable reuse methods. This is largely due to the fact that thermoset polyurethanes cannot be melted to be remolded into other products. However, the long-term need for space to accumulate waste and the increase in landfill costs, as well as the strengthening of environmental regulations and the greater awareness of society to improve the sustainability of current lifestyles, dictate the need to develop and implement alternatives to the treatment of polyurethane waste, preferably by reintroducing it into the consumer chain.
[0004] Molecular depolymerization of polyurethane waste is one of the more interesting strategies for implementing industrial processes based on the circular economy today. In the process, polyurethane waste is converted into the compounds that lead to its synthesis; namely, polyols and diamines from diisocyanates, with the aim of reintroducing them into new polyurethane synthesis processes, thus promoting the economic and environmental advantages that are characteristic of sustainable development and the circular economy [Kemona, A., Piotrowska, M. Polymers, 2020, 12(8), p. 1752].
[0005] The most common chemical methods for depolymerization of polyurethanes are hydrolysis and glycolysis, although strategies combining the two have also been identified [Gerlock J. et al. (1984). Ind. Eng. Chem. Process Des. Dev., 23 (3), p. 545-552]. In depolymerization by hydrolysis, water is the compound that serves as both a urethane bond cleaving agent and a solvent; whereas in the case of depolymerization by glycolysis, an alcohol (e.g., methanol) or a diol (e.g., ethylene glycol, propylene glycol, diethylene glycol) is used in an amount greater than the weight of the polyurethane to be treated (usually 1.5:1 or more) to achieve both functions.
[0006] All polyurethane depolymerization processes described in the prior art to date are based on suspending the polyurethane material in an excess of a protic molecule solvent; i.e. water, diols, alcohols or mixtures thereof, as nucleophiles, with or without a volatile organic co-solvent (usually toluene or tetrahydrofuran THF), and in the presence of carbene-type organic catalysts, quaternary ammonium salts or conventional bases such as NaOH, KOH, etc. (concentration greater than 4N), with low catalytic activity, making it necessary to carry out the process at high temperatures (130-250°C) and long reaction times (>12h), obtaining yields of less than 85% and favoring unwanted side reactions [see, for example, EP0011662B1; US5208379A; WO2010 / 130652A2; US2004127720A1; EP1693409A1; WO 2022 / 042909A1; Gadhave, RV, et al.Open J.Polym.Chem.,2019,9(2),p.39-51].
[0007] Alternatively, depolymerization of polyurethane foam by glycolysis with diols (e.g., ethylene glycol) is a widely described method, which also requires severe reaction conditions [Simón, D. et al. Waste Management, 2018, 16, p. 147-171]. By this strategy, polyurethane waste is suspended in excess polyol (e.g., ethylene glycol) for 6-48 hours at a temperature between 150-280 ° C in the presence of a catalyst (e.g., cyclohexane acid, potassium acetate, titanium butoxide, stannous octoate, etc.). This method produces a two-phase system in which the denser lower phase contains polyurethane glycolysis products, while the upper phase contains excess polyols used as reaction medium. In addition, after the catalytic reaction, it is necessary to eliminate the subsequent expensive step of excess diol by vacuum distillation (100 mbar, 170-180 ° C) in order to obtain a product with a KOH value suitable for possible reuse in new polyurethane synthesis [see EP1693409A1, JP2003064218A].
[0008] In the same sense, glycolysis processes using diethanolamine or ethanolamine have also been described, and effective depolymerization of polyurethanes at temperatures close to 200°C has been observed using tin salts (such as dibutyltin dilaurate, etc.) as catalysts [see dos Santos, LM et al. Polímeros: Ciencia e Tecnología, 2013, 23, 608-613; Jehanno, C. et al. Polymer Chemistry, 2019, 10, 172-186].
[0009] Based on the prior art, there is an urgent need to develop a fast and efficient polyurethane depolymerization method based on mild reaction conditions and using an active reaction medium that is stable over time and fully recyclable and reusable, thereby obtaining a recovered polyol material that is easily separated from the reaction medium and can be reused in the synthesis of new polyurethane without the need for subsequent purification steps. Summary of the invention
[0010] The object of the present invention relates to a method for depolymerizing a polyurethane substance, wherein the method comprises performing the following steps:
[0011] a) mixing a polyurethane material with a depolymerization reaction medium, wherein the depolymerization reaction medium comprises an ionic liquid, a basic catalyst, and a nucleophile; and
[0012] b) obtaining two mutually immiscible fractions from the mixture obtained in step a):
[0013] A first fraction comprising at least one polyol material; and
[0014] The second fraction comprises at least an ionic liquid and a basic catalyst.
[0015] Advantageously, in the method of the present invention:
[0016] The depolymerization reaction medium comprises:
[0017] an ionic liquid in a proportion greater than or equal to 50% w / w relative to the total weight of the depolymerization reaction medium;
[0018] Superbases, which act as basic catalysts; and
[0019] a nucleophile in a proportion less than or equal to 15% w / w relative to the total weight of the depolymerization reaction medium;
[0020] Step a) is carried out at a temperature of 50-100° C. for 2 minutes to 10 hours; and
[0021] Step b) comprises performing the following sub-steps:
[0022] i. adding to the mixture of step a) 4 to 40 times the weight of the depolymerization reaction medium a protic molecular solvent;
[0023] ii. placing the mixture of step i) at a temperature of 20-60°C for at least 1 hour; and
[0024] iii. Separate the obtained fractions.
[0025] Within the scope of the present invention, "ionic liquid" will be understood as any chemical substance formed only by ions and having a melting point below 100°C. Among its physicochemical properties, its almost zero volatility is outstanding, which converts this type of compound into a non-polluting and recyclable alternative to volatile organic solvents. In addition, this compound has excellent thermal stability, a large capacity for dissolving various molecular compounds (including gases), and density, melting point, polarity and miscibility with water or other molecular solvents, which can be adjusted according to the type of anions and cations formed. Similarly, "superbase" will be understood as any organic compound with high proton affinity, which contains two or more basic functional groups and one or more nitrogen atoms (N) forming CN, C=N, C=NC, -NH and / or =NH bonds (where C is the chemical symbol for carbon and H is the chemical symbol for hydrogen), and when added to the reaction, increases the reaction rate. More preferably, "superbase" should be understood to mean any amidine, amidine derivative, guanidine or guanidine derivative, even more preferably pK aThe term "nucleophile" is understood to mean any chemical compound that interacts or reacts with the carbon of the carbonyl group of the carbamate bond, resulting in the cleavage of the bond. More preferably, "nucleophile" is understood to mean water, alcohol, primary amine, secondary amine, or any possible combination thereof. Finally, the term "protic molecule solvent" is understood to mean any polar solvent consisting of isolated molecules capable of forming hydrogen bonds with other electronegative molecules, donating and accepting protons, having a boiling point of less than or equal to 100°C, and in which the polyol material recovered by the method of the present invention is not soluble.
[0026] The process of the present invention represents a sustainable alternative to the polyurethane depolymerization processes known to date. First, the process allows the depolymerization of polyurethane at temperatures below 100°C and reaction times of less than 10 hours, which simplifies the operating system and facilitates the control and safety of the process. Secondly, the process is characterized by the simultaneous use of ionic liquids and super bases to form the depolymerization reaction medium. The ionic liquid is the main component of the reaction medium, and the use of ionic liquids instead of volatile organic solvents or diols not only provides better regulation for the depolymerization of polyurethanes, but also solves the problems of solvent emissions (due to their low volatility) and waste generation (due to their easy recovery and reuse without the need for expensive purification processes). In turn, compared with conventional alkaline catalysts (e.g., NaOH, KOH, carbenes, amines), super bases provide much higher catalytic activity in non-aqueous reaction media and / or at low water content, and have higher stability over time and are easy to recycle and reuse. Finally, since the process is carried out at a temperature below 100°C, it can be carried out at atmospheric pressure using low-boiling nucleophiles such as water, alcohols such as methanol or ethanol, or primary amines such as butylamine, which determines that the polyol species produced by the depolymerization process do not require a subsequent purification step. These conditions are significantly different from the traditional glycolysis process, in which the low efficiency of the catalyst determines the use of high reaction temperatures (130-280°C). This makes it necessary to use diols to reduce the risk, because their boiling points are close to or above 200°C, but the excess diol must be separated to obtain polyols that can be reused in the synthesis of new polyurethanes. In addition, in the process of the present invention, a low-boiling nucleophile is used in a concentration of less than or equal to 15% w / w, so that the nucleophile can be easily completely removed, because the amount is almost consumed during the depolymerization reaction of the polyurethane species. Its final possible excess can be easily removed by evaporation or by washing with a protic molecule solvent, preferably water, to achieve separation of the polyol species from the reaction medium.
[0027] In a preferred embodiment of the present invention, the polyurethane material comprises thermosetting polyurethane; more preferably, the polyurethane material comprises polyurethane foam.
[0028] In another preferred embodiment of the present invention, in step a), the polyurethane material is mixed with the depolymerization reaction medium in a mass ratio of 1:20 to 1:1; more preferably, 1:15 to 1:3, even more preferably, 1:10 to 1:5.
[0029] In another preferred embodiment of the present invention, step a) is carried out at a temperature of 80-100° C. and / or for 2 to 8 hours. More preferably, it is carried out at a temperature of 90-98° C. and / or for 3 to 7 hours.
[0030] In another preferred embodiment of the present invention, step a) is carried out in a depolymerization reaction medium, and the depolymerization reaction medium contains the ionic liquid in a proportion of 50% w / w to 85% w / w, more preferably 65% w / w to 80% w / w, relative to the total weight of the depolymerization reaction medium.
[0031] In another preferred embodiment of the present invention, step a) is carried out in a depolymerization reaction medium comprising a nucleophile in a proportion of 1% w / w to 15% w / w, more preferably 5% w / w to 15% w / w, relative to the total weight of the depolymerization reaction medium.
[0032] In another preferred embodiment of the present invention, in step b), the amount of the protic molecule solvent added is 5 to 15 times the weight of the depolymerization reaction medium.
[0033] In another preferred embodiment of the present invention, step a) is carried out with a nucleophile comprising water, alcohol, amine, or any possible combination thereof. More preferably, the nucleophile comprises at least 80% water due to its higher nucleophilic ability and low boiling point.
[0034] In a preferred embodiment of the present invention, sub-step i) is carried out with a protic molecular solvent comprising water, methanol, ethanol, isopropanol, or any possible combination thereof. More preferably, the protic molecular solvent comprises at least 80% water.
[0035] In another preferred embodiment of the present invention, step a) is carried out with an ionic liquid comprising:
[0036] a cation selected from dialkylimidazolium, tetraalkylammonium, dialkylpiperidinium, alkylpyridinium, dialkylpyrrolidonium and / or tetraalkylphosphonium; and / or
[0037] Anions are selected from fluoride, chloride, bromide, iodide, acetate, trifluoroacetate, formate and / or carbonate.
[0038] More preferably, the ionic liquid comprises 1-butyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium acetate, 1-butyl-3-methylpyridinium chloride, 1-butyl-3-methylpyridinium bromide, 1-butyl-3-methylpyridinium iodide, 1-butyl-1-methylpiperidinium chloride, 1-butyl-1-methylpiperidinium bromide, 1-butyl-1-methylpiperidinium iodide, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium bromide, 1-butyl-3-methylimidazolium iodide, 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium iodide, 1-butyl-4-methylpyridinium chloride, 1-butyl-3-methylimidazolium formate, 1-butyl-1-methylpiperidinium chloride, 1-butyl-1-methylpiperidinium bromide, 1-butyl-1-methylpiperidinium iodide, -hexyl-3-methylimidazole, 1-hexyl-3-methylimidazole bromide, 1-hexyl-3-methylimidazole iodide, 1-octyl-3-methylimidazole chloride, 1-octyl-3-methylimidazole bromide, 1-octyl-3-methylimidazole iodide, 1-allyl-3-methylimidazole chloride, 1-butyl-3-methylimidazole acetate, 1-butyl-3-methylimidazole bromide, 1-ethyl-2-methylpyridine bromide, N-ethylpyridine bromide, 1-butyl-3-methylimidazole chloride, 1-butyl-1-methylpyrrole chloride, 1-butyl-1-methylpiperidinium iodide, tetrabutylphosphine bromide, tetrabutylphosphine chloride, 1-butyl-2-methylpyridine chloride, 1-ethyl-1-methylpiperidinium chloride, or any possible combination thereof.
[0039] In another preferred embodiment of the present invention, step a) is carried out with a superbase comprising at least a bicyclic amidine, a bicyclic amidine derivative, a guanidine, a guanidine derivative, or any possible combination thereof. More preferably, the superbase used in the process of the present invention comprises 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,5-diazabicyclo[4.3.0]non-5-ene (DBN), 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD), tetramethylguanidine (TMG), or any possible combination thereof.
[0040] In another preferred embodiment of the present invention, the method comprises performing at least one of the following additional steps:
[0041] reusing the first fraction in the synthesis of new polyurethane; and / or
[0042] The second fraction is reused in step a) of the novel process for depolymerizing polyurethane substances.
[0043] In another preferred embodiment of the present invention, the method comprises an additional step of drying the first and / or second fraction until the water content of the fraction is reduced to a value of less than 1% w / w. In the context of the present invention, "drying" is understood to be any physical or chemical operation to remove water; preferably freeze-drying, vacuum evaporation, heating, distillation, resin adsorption, or any possible combination thereof.
[0044] Furthermore, the two preferred embodiments described above may comprise a prior step of treating the second fraction with a hydrophobic adsorbent; preferably, the hydrophobic adsorbent is activated carbon or a polystyrene resin.
[0045] In another preferred embodiment of the present invention, sub-step iii) comprises a process of centrifugation, decantation, filtration, vacuum filtration, resin adsorption, or any possible combination thereof.
[0046] In another preferred embodiment of the present invention, the method of the present invention comprises an additional step of verifying the progress and completion of step a) and / or b). Preferably, the additional step comprises at least one of the following sub-steps:
[0047] During step a), a uniform sample (e.g., 0.2 mL) of the reaction medium is taken at different time intervals and suspended in 10 volumes of an aprotic polar solvent (e.g., acetone, dimethyl sulfoxide (DMSO) or tetrahydrofuran) capable of dissolving the polymeric polyol, to obtain a solution free of suspended solids when step a) is completely completed;
[0048] The first dried fraction was analyzed by attenuated total reflection infrared spectroscopy combined with Fourier transform infrared spectroscopy (ATR-FTIR) to observe the characteristic band of carbamate bonds (1700 cm -1 -1740cm -1 ) is missing; and / or
[0049] According to ASTM D-4274-16 (2016) standard, the hydroxyl value (mg KOH / g sample) is determined by titrating the first dried fraction with phthalic anhydride / pyridine to quantify the presence of hydroxyl groups in the recovered solid fraction. Since the polyol contains multiple hydroxyl groups, the higher the value, the greater the amount of polyol present in the fraction, indicating the correct depolymerization of the polyurethane material according to the method of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 Five depolymerization reaction mixtures according to preferred embodiments of the present invention are shown. Figure 1 A) and after incubation at 95°C with magnetic stirring for 4 h ( Figure 1B), the depolymerization reaction mixture contained 65% w / w of different ionic liquids, 20% w / w of ground polyurethane foam, 10% w / w of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) and 5% w / w of water.
[0051] Figure 2 Shown is the evolution of depolymerization over time for polyurethane rods contacted with a depolymerization reaction medium containing 65% w / w 1-butyl-3-methylimidazole chloride ([Bmim][Cl]), 20% w / w DBU and 15% w / w water at 95°C for 2 minutes.
[0052] Figure 3 Shown are the results of centrifugation of fractions obtained after depolymerization of a polyurethane foam material according to a preferred embodiment of the present invention: 4 hours at 95° C. in a reaction medium comprising ([Bmim][Cl]), DBU and water (left); and 4 hours at 95° C. in a reaction medium comprising 1-butyl-3-methylimidazole bromide ([Bmim][Br]), DBU and water (right).
[0053] Figure 4 The ATR-FTIR spectra of the following materials are shown: (1) a ground thermosetting polyurethane foam material; (2) a commercial polyol material for industrial use; (3) a polyol material recovered by the method of the present invention using a depolymerization reaction medium (containing 65% w / w 1-butyl-3-methylimidazolium acetate ([Bmim][Ac]), 20% w / w DBU and 15% w / w water); (4) a polyol material recovered by the method of the present invention using a depolymerization reaction medium (containing 65% w / w [Bmim][Cl], 20% w / w DBU and 15% w / w water); (5) a polyol material recovered by the method of the present invention using a depolymerization reaction medium (containing 65% w / w 1-ethyl-3-methylimidazolium chloride ([Emim][Cl]), 20% w / w DBU and 15% w / w water). The characteristic bands of urethane bonds (1720-1740 cm -1 ) are indicated by vertical dashed lines.
[0054] Figure 5 The ATR-FTIR spectra of the following materials are shown: (1) ground polyurethane foam waste; (2) polyurethane foam synthesized from commercial polyol materials for industrial use; (3) polyurethane foam synthesized from polyol materials recycled by a preferred embodiment of the method of the present invention. The characteristic band of urethane bonds (1720-1740 cm -1 ) are represented by gray stripes.
[0055] Figure 6The ATR-FTIR spectra of a polyurethane foam material (1) and the ATR-FTIR spectrum of a solid fraction obtained after applying the depolymerization process of the present invention to the foam in a reaction medium containing no ionic liquid or no superbase and using water as a nucleophile, the reaction medium being: (2) 15% w / w 1,5-diazabicyclo[4.3.0]non-5-ene (DBN) in water; (3) 15% w / w tetramethylguanidine (TMG) in water; (4) 66% w / w [Bmim][Cl] in water; (5) 66% w / w [Bmim][Br] in water. The characteristic bands of urethane bonds (1700-1740 cm -1 ) is represented by two vertical dashed lines.
[0056] Figure 7 The ATR-FTIR spectrum of the polyurethane foam material (1) and the ATR-FTIR spectra (2-4) of the solid fraction recovered after applying a depolymerization method to the foam according to a preferred embodiment of the present invention are shown. Specifically, the reaction was carried out at 95°C for 6 hours in the following depolymerization reaction medium: (2) containing 1-butyl-1-methylpyrrole chloride ([BmPyrr][Cl]), DBU and water; (3) containing 1-butyl-1-methylpiperidinium iodide ([BmPip][I]), DBU and water; or (4) containing tetrabutylphosphine bromide ([TBP][Br]), DBU and water. The characteristic bands of carbamate bonds (1700-1740cm -1 ) is represented by two vertical dashed lines.
[0057] Figure 8 The ATR-FTIR spectrum of the polyurethane foam material (1) and the ATR-FTIR spectra of the solid fraction recovered after applying the depolymerization method to the foam according to a preferred embodiment of the present invention (2-5) are shown. Specifically, the reaction was carried out at 95°C for 6 hours in the following depolymerization reaction medium: (2) containing [Bmim][Ac], TMG and water; (3) containing [Bmim][Cl], TMG and water; (4) containing 1-allyl-3-methylimidazole chloride ([Amim][Cl]), TMG and water; or (5) containing [TBP][Br], TMG and water. The characteristic bands of carbamate bonds (1700-1740cm -1 ) is represented by two vertical dashed lines.
[0058] Fig. 9 The ATR-FTIR spectra of a polyurethane foam material (1) and the ATR-FTIR spectrum of a solid polyol recovered after depolymerization of the foam in a reaction medium containing [Bmim][Cl], DBN and water at 95°C for 6 hours (2) are shown. The characteristic bands of urethane bonds (1700-1740 cm-1 ) is represented by two vertical dashed lines.
[0059] Fig.10 The ATR-FTIR spectrum of the polyurethane foam material (1) and the ATR-FTIR spectra of the solid fraction recovered after applying the depolymerization method to the foam according to a preferred embodiment of the present invention (2, 3) are shown. Specifically, the reaction was carried out at 95°C for 6 hours in the following depolymerization reaction medium: (2) containing 1-butyl-2-methylpyridinium chloride ([BmPyr][Cl]), DBU and water; or (3) containing N-ethylpyridinium bromide ([Epyr][Br]), DBU and water. The characteristic bands of the carbamate bond (1700-1740cm -1 ) is represented by two vertical dashed lines.
[0060] Fig.11 The ATR-FTIR spectrum of the polyurethane foam material (1) and the ATR-FTIR spectrum of the solid fraction recovered after applying the depolymerization method to the foam according to a preferred embodiment of the present invention (2-4) are shown. Specifically, the reaction was carried out at 95°C for 6 hours in the following depolymerization reaction medium: (2) containing [Bmim][Ac], DBU and methanol; (3) containing [Bmim][Cl], TMG and ethanol; or (4) containing [BmPip][I], TMG and ethanol. The characteristic bands of the urethane bond (1700-1740cm -1 ) is represented by two vertical dashed lines.
[0061] Fig.12 The ATR-FTIR spectrum of a polyurethane foam material (1) and the ATR-FTIR spectra of a solid fraction recovered after a depolymerization process is applied to the foam according to a preferred embodiment of the present invention (2, 3) are shown. Specifically, the depolymerization reaction medium contains: (2) [Bmim][Cl], DBU and 1-butylamine; or (3) [TBP][Br], DBN and 1-butylamine. The characteristic bands of urethane bonds (1700-1740 cm -1 ) is represented by two vertical dashed lines.
[0062] Fig.13The ATR-FTIR spectrum of a polyurethane foam material (1) and the ATR-FTIR spectra of a solid fraction recovered after applying a depolymerization process to the foam according to a preferred embodiment of the present invention (2-7) are shown. Specifically, the depolymerization reaction medium contains: (2) [Bmim][Cl], 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) and water; (3) [BmPyrr][Cl], TBD and water; (4) [BmPip][I], TBD and water; (5) [BmPyr][Cl], TBD and water; (6) [TBP][Br], TBD and water; or (7) 1-ethyl-2-methylpyridinium bromide ([EmPyr][Br]), TBD and water. The characteristic bands of carbamate bonds (1700-1740 cm -1 ) is represented by two vertical dashed lines.
[0063] Fig.14 The ATR-FTIR spectrum of a polyurethane foam material (1) and the ATR-FTIR spectra of a solid fraction recovered after applying a depolymerization process to the foam according to a preferred embodiment of the present invention (2, 3) are shown. Specifically, the depolymerization reaction medium contains: (2) [Bmim][Cl], TBD and acetone acetal; or (3) [BmPyrr][Cl], TBD and acetone acetal. The characteristic bands of urethane bonds (1700-1740 cm -1 ) is represented by two vertical dashed lines.
[0064] Fig.15a The ATR-FTIR spectrum of the oxybis(2,1-ethylenediyl)bis(phenylcarbamate) substance and the ATR-FTIR spectrum of the product isolated after the carbamate bond is broken by placing the substance in a reaction medium at 95°C for 4 hours. The reaction medium contains: (2) [Bmim][Cl], DBU and water; (3) [Bmim][Cl], TBD and water; (4) [Bmim][Cl], pyrrolidine and water; (5) [Bmim][Cl], tert-butylamine and water; or (6) [Bmim][Cl], triethylamine and water. The characteristic bands of the carbamate bond (1700-1740cm -1 ) is represented by two vertical dashed lines. Fig.15b HPLC chromatograms (2-6) of the carbamate substance (1) and the separated products after the cleavage of the carbamate bond under the above experimental conditions are shown.
[0065] Fig.16 The oxybis(2,1-ethylenediyl)bis(phenylcarbamate) substance is placed in a reaction medium at 95°C for 4 hours, and the product is separated after the carbamate bond is broken: (A) 1 H-NMR spectrum, (B)13 C-NMR spectrum, (C) ATR-FTIR spectrum; the reaction medium contained [Bmim][Cl] (as ionic liquid), DBU (as super base) and water (as nucleophile).
[0066] Fig.17a (A) Oxybis(2,1-ethylenediyl)bis(phenylcarbamate) 1 H-NMR spectrum; (B) The product isolated after the cleavage of the carbamate bond of oxybis(2,1-ethylenediyl)bis(phenylcarbamate) 1 H-NMR spectrum; (C) using [Bmim][Cl], water and 12.3 equivalents of DBU as the reaction medium to obtain the reaction product 1 H-NMR spectrum; (D) using [Bmim][Cl], water and 5 equivalents of DBU as the reaction medium of the reaction product 1 H-NMR spectrum; (E) The reaction product obtained using [Bmim][Cl] and water as the reaction medium (without DBU) 1 H-NMR spectrum. Fig.17b HPLC chromatograms corresponding to these compounds are shown.
[0067] Fig.18 Shown are the ATR-FTIR spectra of (1) a polyurethane foam material and the ATR-FTIR spectra (2-6) of a solid fraction recovered after applying a depolymerization process to the foam in a reaction medium containing: (2) [Bmim][Cl], DBU and water; (3) [Bmim][Cl], TBD and water; (4) [Bmim][Cl], pyrrolidine and water; (5) [Bmim][Cl], tert-butylamine and water; or (6) [Bmim][Cl], triethylamine and water. The characteristic bands of urethane bonds (1700-1740 cm -1 ) is represented by two vertical dashed lines.
[0068] Fig.19 Shown are HPLC chromatograms of (1) oxybis(2,1-ethylenediyl)bis(phenylcarbamate) material and HPLC chromatograms of products separated after the carbamate bond is broken by placing the material in a reaction medium at 95°C for 4 hours, wherein the reaction medium contains: (2) [Bmim][Cl], DBU and water; (3) [Bmim][Ac], DBU and water; (4) [TBP][Br], DBU and water; or (5) [BmPyr][Cl, DBU and water. DETAILED DESCRIPTION
[0069] As described in the previous section, the object of the present invention relates to a method for depolymerizing a polyurethane substance, which is carried out at a temperature below 100° C. in a reaction medium comprising an ionic liquid, a basic catalyst and a nucleophile, by a hydrolysis reaction, an alcoholysis reaction, an aminolysis reaction, or any possible combination thereof. Preferably, the polyurethane substance comprises a thermosetting polyurethane; more preferably, the polyurethane substance comprises a polyurethane foam, typically from removed post-consumer products and post-production waste.
[0070] The ionic liquid comprises a cation with high charge delocalization; preferably, the ionic liquid comprises dialkyl imidazole, tetraalkyl ammonium, dialkyl piperidine, alkyl pyridine, dialkyl pyrrolidine and / or tetraalkyl phosphine, and / or an anion having hydrophilicity and no charge delocalization, which preferably comprises fluoride, chloride, bromide, iodide, acetate, trifluoroacetate, formate and / or carbonate. More preferably, the ionic liquid used in the method of the present invention includes 1-butyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium acetate, 1-butyl-3-methylpyridinium chloride, 1-butyl-3-methylpyridinium bromide, 1-butyl-3-methylpyridinium iodide, 1-butyl-1-methylpiperidinium chloride, 1-butyl-1-methylpiperidinium bromide, 1-butyl-1-methylpiperidinium iodide, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium bromide, 1-butyl-3-methylimidazolium iodide, 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium iodide, 1-butyl-4-methylpyridinium chloride, 1-butyl-3-methylimidazolium carboxylic acid salt, 1-hexyl-3-methylimidazole chloride, 1-hexyl-3-methylimidazole bromide, 1-hexyl-3-methylimidazole iodide, 1-octyl-3-methylimidazole chloride, 1-octyl-3-methylimidazole bromide, 1-octyl-3-methylimidazole iodide, 1-allyl-3-methylimidazole chloride, 1-butyl-3-methylimidazole acetate, 1-butyl-3-methylimidazole bromide, 1-ethyl-2-methylpyridine bromide, N-ethylpyridine bromide, 1-butyl-3-methylimidazole chloride, 1-butyl-1-methylpyrrole chloride, 1-butyl-1-methylpiperidinium iodide, tetrabutylphosphine bromide, tetrabutylphosphine chloride, 1-butyl-2-methylpyridine chloride, 1-ethyl-1-methyl-piperidinium chloride or any possible combination thereof. Regarding the concentration of the ionic liquid in the reaction medium, relative to the total weight of the depolymerization reaction medium, the proportion of the ionic liquid is greater than or equal to 50% w / w; preferably between 50% w / w-85% w / w, more preferably between 65% w / w-80% w / w.
[0071] The basic catalyst comprises a superbase, and the superbase preferably contains at least a bicyclic amidine, a bicyclic amidine derivative, a guanidine, a guanidine derivative, or any possible combination thereof. These types of catalysts are more active in non-aqueous systems and / or with low water content than conventional basic catalysts (e.g., sodium hydroxide (NaOH) or potassium hydroxide (KOH)), and have higher stability over time, and conventional basic catalysts will carbonize over time. Even more preferably, the basic catalyst used in the method of the present invention includes 1,8-diazabicyclo [5.4.0] undecyl-7-ene (DBU), 1,5-diazabicyclo [4.3.0] non-5-ene (DBN), 1,5,7-triazabicyclo [4.4.0] dec-5-ene (TBD), tetramethylguanidine (TMG), or any possible combination thereof.
[0072] The nucleophile preferably comprises water (depolymerization by hydrolysis), alcohol (depolymerization by alcoholysis), amine (depolymerization by aminolysis), or any possible combination thereof, in a proportion less than or equal to 15% w / w relative to the total weight of the depolymerization reaction medium. More preferably, the nucleophile comprises at least 80% water, due to its higher nucleophilicity, immiscibility with the polyol and ease of removal by evaporation. As for the concentration of the nucleophile in the depolymerization reaction medium, the proportion of the nucleophile is preferably 1% w / w-15% w / w, more preferably 5% w / w-15% w / w, relative to the weight of the medium.
[0073] Under constant stirring (mechanical, magnetic, etc.), the mixture of the polyurethane substance and the reaction medium is incubated at a controlled temperature of 50-100° C., preferably 80-100° C., more preferably 90-98° C., even more preferably 95° C. for 2 minutes to 10 hours; preferably 2 to 8 hours, even more preferably 3 to 7 hours.
[0074] Next, the mixture is washed by adding 4 to 40 times, preferably 5 to 15 times, the weight of the reaction medium in a protic molecule solvent. This washing of the mixture causes the polyol material (a component of the polyurethane material) to precipitate because it is soluble in the solvent. Preferably, the protic molecule solvent comprises water, methanol, ethanol, isopropanol, or any possible combination thereof, more preferably at least 80% water.
[0075] The heterogeneous mixture or suspension obtained after adding the protic molecular solvent is kept under constant stirring (mechanical, magnetic, etc.) at a temperature of 20-60° C. for at least 1 hour, preferably 2 hours at 40° C. Then, the reaction mixture is separated, usually by filtration or centrifugation, to obtain two fractions: a first fraction or semi-solid fraction, and a second fraction or single-phase liquid fraction.
[0076] The single-phase liquid fraction contains all the components of the reaction medium that are soluble in the protic molecular solvent, i.e. the ionic liquid and the catalyst. The mixture can be filtered through a hydrophobic adsorbent (e.g. activated carbon or polystyrene resin) to remove any diamine residues and prevent the fraction from becoming black. After the filtration process, the fraction can be concentrated, e.g. by evaporation under reduced pressure to remove water, to a final concentration of less than 1% w / w, and can thus be directly reused in a new polyurethane chemical depolymerization process.
[0077] The semi-solid fraction contains mainly polyol species. In order to examine its molecular properties, this fraction is dried, preferably by freeze drying or evaporation under reduced pressure, to reduce the water content to a level below 1% w / w. Subsequently, three different analytical tests can be performed to verify the complete depolymerization of the polyurethane species; namely, solubility in organic solvents, attenuated total reflection infrared spectroscopy combined with Fourier transform infrared spectroscopy (ATR-FTIR) and hydroxyl number determination.
[0078] Unlike polyols, polyurethanes are insoluble in all conventional polar organic solvents (e.g., acetone or dimethyl sulfoxide (DMSO)). This difference allows the properties of the semi-solid fraction produced after the depolymerization process of the present invention to be examined by a simple solubility test. Preferably, 20 mg of the resulting semi-solid fraction is filtered and dried, then resuspended in 2 mL of DMSO. If depolymerization is complete, the semi-solid fraction will be completely dissolved in the organic solvent, indicating a loss of polymer integrity.
[0079] Molecular confirmation of the success of the depolymerization reaction can be performed by ATR-FTIR analysis of the first dried fraction. -1 The absence of the characteristic bands of carbonyl groups (CO) forming urethane bonds (-NH-CO-O-) between them would confirm the correct depolymerization of the polyurethane material.
[0080] Similarly, the hydroxyl value (mg KOH / g sample) is determined by titrating the first dried fraction with phthalic anhydride / pyridine according to ASTM D-4274-16 (2016) standard to quantify the presence of hydroxyl groups in the fraction. Since the polyol contains multiple hydroxyl groups, the higher the value, the greater the amount of polyol present in the fraction, indicating the correct depolymerization of the polyurethane material according to the method of the present invention.
[0081] Example
[0082] Various embodiments of the present invention are described in detail below, which show that in order to carry out the depolymerization of polyurethane materials at a temperature of 50-100°C for less than 10 hours (so that the recovered polyol does not require a subsequent purification step), it is strictly necessary:
[0083] - The polymerization medium comprises an ionic liquid, a superbase and a nucleophile;
[0084] - ionic liquid is the main component of the reaction medium;
[0085] - the basic catalyst is a superbase;
[0086] - the concentration of nucleophile is less than or equal to 15% w / w relative to the total weight of the depolymerization reaction medium;
[0087] - The amount of protic molecular solvent used is 4 to 40 times the weight of the depolymerization reaction medium to stop the reaction.
[0088] To this end, in addition to the visible examples (see Examples 1-3), the results of the above analytical tests will be shown to confirm the complete depolymerization of the polyurethane material (i.e., solubility test, ATR-FTIR spectroscopy analysis and determination of hydroxyl value) when the following depolymerization reaction medium is used:
[0089] - using the same superbase and nucleophile, but different ionic liquids (see Examples 4, 7 and 10);
[0090] - using the same ionic liquid and nucleophile, but different superbases (see Examples 4, 8, 9 and 14);
[0091] - using the same ionic liquid and superbase, but different nucleophiles (see Examples 4, 8, 11, 12, 13, 14 and 15);
[0092] - Incomplete depolymerization, no ionic liquid or no superbase (see Example 6);
[0093] - Using a base instead of a superbase as catalyst (see Example 20).
[0094] Similarly, it was demonstrated that the polyol fraction recovered by the process of the present invention can be reused as starting material for the synthesis of new polyurethanes by any of the protocols known in the art (see Example 5).
[0095] Finally, the influence of the reaction medium components was also evaluated in a simple carbamate model: oxybis(2,1-ethylenediyl)bis(phenylcarbamate), which was synthesized and purified according to the method described in Motokucho, S. et al. J. Polym. Sci. A Polym. Chem. 2017, 55(12), p. 2004-2010. Using this model instead of polyurethane foam as the starting material, the development of the conversion of the carbamate group can be monitored by nuclear magnetic resonance (NMR) or high performance liquid chromatography (HPLC) techniques, providing evidence for the cleavage of the bond that is key to the depolymerization of polyurethane.
[0096] Tables 1 and 2 include abbreviations for the ionic liquids and superbases used in the depolymerization reaction medium of the various embodiments of the invention presented herein.
[0097] Table 1. Ionic liquids used in embodiments of the present invention.
[0098] abbreviation Compound Name [Amim][Cl] 1-Allyl-3-methylimidazole chloride [Bmim][Ac] 1-Butyl-3-methylimidazolium acetate [Bmim][Br] 1-Butyl-3-methylimidazole bromide [Bmim][Cl] 1-Butyl-3-methylimidazole chloride [BmPip][I] 1-Butyl-1-methylpiperidinium iodide [BmPyr][Cl] 1-Butyl-2-methylpyridinium chloride [BmPyrr][Cl] 1-Butyl-1-methylpyrrole chloride [Emim][Cl] 1-Ethyl-3-methylimidazole chloride [EmPyr][Br] 1-Ethyl-2-methylpyridinium bromide [EPyr][Br] N-Ethylpyridinium bromide [Omim][Cl] 1-Octyl-3-methylimidazole chloride [TBP][Br] Tetrabutylphosphonium bromide
[0099] Table 2. Superbases used in embodiments of the invention.
[0100] abbreviation Compound Name DBN 1,5-Diazabicyclo[4.3.0]non-5-ene DBU 1,8-Diazabicyclo[5.4.0]undec-7-ene TBD 1,5,7-Triazabicyclo[4.4.0]dec-5-ene TMG N,N,N′,N′-Tetramethylguanidine
[0101] Example 1 : In a depolymerization reaction medium containing [Bmim][Cl], [Bmim][Br], [Bmim][I], [Emim][Cl] or [Omim][Cl] as an ionic liquid, DBU as a superbase and water as a nucleophile, a polyurethane foam material (PU) was depolymerized at 95°C for 4 hours.
[0102] As an illustration of the present invention, Figure 1 The evolution of five different reaction media during the depolymerization of polyurethane foam according to a preferred embodiment of the process of the present invention is shown. In particular, depolymerization reaction media based on a combination of [Bmim][Cl], [Bmim][Br], [Bmim][I], [Emim][Cl] or [Omim][Cl] (65% w / w, ionic liquid) with DBU (20% w / w, superbase) and water (15% w / w, nucleophile) were used to treat ground polyurethane foam material (25% w / w, relative to the total mass of depolymerization reaction medium). The image shows the appearance of the depolymerization reaction mixture at the start of the reaction ( Figure 1 A), and the appearance after incubation at 95°C under magnetic stirring for 4 h ( Figure 1 B).
[0103] Example 2 : Time evolution of the depolymerization of PU foam materials in a depolymerization reaction medium containing [Bmim][Cl] as ionic liquid, DBU as superbase and water as nucleophile.
[0104] Figure 2 The time evolution of a polyurethane foam mass (0.2 g) immersed in 3 g of a depolymerization reaction medium (based on [Bmim][Cl] (65% w / w), DBU (20% w / w) and water (15% w / w)) at 95°C under stirring is shown by images taken over a 2-minute period.
[0105] Example 3: After depolymerizing PU foam material at 95°C for 4 hours in a depolymerization reaction medium containing [Bmim][Cl] or [Bmim][Br] as an ionic liquid, DBU as a superbase and water as a nucleophile, the polyol is separated and recovered.
[0106] Figure 3 Shown is the polyol recovered by centrifugation after depolymerization of ground polyurethane foam material (25% w / w relative to the total mass of the system) at 95°C for 4 hours in a depolymerization reaction medium containing [Bmim][Cl] or [Bmim][Br] (65% w / w), DBU (20% w / w) and water (15% w / w) under constant stirring. After this period, 20 mL of water was added.
[0107] Example 4 : PU foam was depolymerized at 95°C for 4 hours in a depolymerization reaction medium containing [Bmim][Ac], [Bmim][Cl] or [Emim][Cl] as an ionic liquid, DBU as a superbase and water as a nucleophile.
[0108] In three 50mL screw-cap containers, 1g of [Bmim][Ac], [Bmim][Cl] or [Emim][Cl] was added and mixed with 0.3g DBU, 0.25g water and 0.4g ground polyurethane foam respectively. The three containers were kept closed and mechanically stirred at 95°C for 4 hours. After this period of time, 20mL of water was added to each container and stirred at room temperature for 1 hour. Each resulting suspension was then centrifuged at 7000rpm for 20 minutes. The resulting precipitate was separated by decantation and filtration through a nylon membrane (0.45 micron) and finally dried to constant weight in a vacuum oven at 80°C. The dried product was analyzed by the following control test:
[0109] Horizontal Control 1 - Solubility Test. 20 mg of each dry polyol was added to 2 mL of dimethyl sulfoxide (DMSO) and completely dissolved, resulting in a translucent solution in all cases. Since polyurethane is insoluble in DMSO, while polyols are soluble in DMSO, this result indicates that the polyurethane foam material has depolymerized.
[0110] Level control 2-ATR-FTIR spectroscopy analysis (see Figure 4 Each of the obtained dry polyols was analyzed by ATR-FTIR and its spectra (3-5) were compared with those of the original polyurethane foam material (1) and the commercial polyol material (2). In no case was the characteristic band of urethane bonds (1700-1740 cm -1) (see spectra 3, 4 and 5), a signal similar to that of the commercial polyol (spectrum 2) was obtained. This confirms the correct depolymerization of the polyurethane foam material according to the process of the invention.
[0111] Horizontal control 3-hydroxyl value determination. Based on ASTM D-4274-16 (2016) standard, the following hydroxyl values were obtained by titrating different dry polyols with phthalic anhydride / pyridine:
[0112] -PU standard: 9.45mg KOH / g polyol
[0113] - Reaction medium [Bmim][Ac] + DBU + water: 57.41 mg KOH / g polyol
[0114] - Reaction medium [Bmim][Cl] + DBU + water: 52.52 mg KOH / g polyol
[0115] - Reaction medium [Emim][Cl] + DBU + water: 55.61 mg KOH / g polyol
[0116] A higher hydroxyl number represents a higher concentration of polyols in the sample, since said compounds are characterized by having a plurality of hydroxyl groups. Thus, since the hydroxyl numbers obtained for the different solid fractions are much higher than the hydroxyl number of the starting polyurethane foam material, correct depolymerization thereof is again confirmed according to these preferred embodiments of the process of the invention.
[0117] Example 5 : The polyol fraction recovered by the method of the present invention is reused in the synthesis of new polyurethane.
[0118] Figure 4 The ATR-FTIR spectra of the following materials are shown: (1) ground polyurethane foam material; (2) polyurethane foam synthesized from industrial commercial polyol material; (3) polyurethane foam synthesized from polyol material recovered by a preferred embodiment of the method of the present invention. That is, for the polyol material recovered according to the preferred embodiment of the method of the present invention, the depolymerization reaction medium used contained 65% w / w [Bmim][Cl], 20% w / w DBU and 15% w / w water. The depolymerization reaction was carried out by mixing 40% of the polyurethane foam waste and 60% of the depolymerization reaction medium and maintaining continuous stirring at 95°C for 4 hours. It can be observed that the three polymerization products have a characteristic region of urethane bonds (1700-1740cm -1 ) has one band, which shows that the first fraction obtained by the process of the present invention can be used as a starting material for the synthesis of new polyurethanes by any scheme known in the prior art.
[0119] Example 6: Depolymerization of PU foam material in incomplete depolymerization reaction medium.
[0120] In four 50 mL screw-cap containers, four incomplete depolymerization reaction media were prepared by adding 0.4 g DBN, or 0.4 g TMG, or 2.4 g [Bmim] [Cl] or 2.4 g [Bmim] [Br], respectively, mixed with 2.6 g, 2.6 g, 0.6 g or 0.6 g water, respectively. Finally, 1 g of ground polyurethane foam was added to each container. The four containers were kept closed and mechanically stirred at 95° C. for 6 hours, and then 20 mL of water was added to stop the reaction. The precipitated product was subjected to the same sample separation, drying and analysis methods described in Example 4, showing the following results:
[0121] Horizontal control 1 - Solubility test. Addition of 20 mg of each of the obtained dry solids to 2 mL of DMSO resulted in an insoluble precipitate in all cases, indicating that depolymerization of the polyurethane foam material could not proceed under these conditions.
[0122] Level control 2-ATR-FTIR spectroscopy analysis (see Figure 6 Each of the dried products obtained was analyzed by ATR-FTIR and its spectra (2-5) were compared with the spectrum (1) of the original polyurethane foam material. In all cases (spectra 2-5), the characteristic bands of urethane bonds (1700-1740 cm -1 ), thereby identifying it as a non-depolymerized polyurethane. This experiment demonstrates the inefficiency of the process at temperatures below 100°C when an ionic liquid or a superbase is not simultaneously present in the depolymerization reaction medium.
[0123] Level comparison 3-hydroxyl value determination. Since the hydroxyl values obtained for the different solid fractions are very similar to those of the starting polyurethane foam material, the inefficiency of the depolymerization process under these conditions is again confirmed:
[0124] -PU standard: 9.45mg KOH / g polyol
[0125] - Reaction medium [Bmim][Cl] + water: 9.52 mg KOH / g polyol
[0126] - Reaction medium [Bmim] [Br] + water: 9.85 mg KOH / g polyol
[0127] -Reaction medium DBU + water: 11.25 mg KOH / g polyol
[0128] -Reaction medium DBN + water: 12.75 mg KOH / g polyol
[0129] Example 7: PU foam was depolymerized at 95°C for 6 hours in a depolymerization reaction medium containing [BmPyrr][Cl], [BmPip][I] or [TBP][Br] as ionic liquid, DBU as superbase and water as nucleophile.
[0130] In three 50 mL screw-cap containers, 2 g of [BmPyrr][Cl], [BmPip][I] or [TBP][Br] was added and mixed with 0.4 g of DBU, 0.6 g of water and 1 g of ground polyurethane foam. The three containers were kept sealed and mechanically stirred at 95°C for 6 hours, and then 20 mL of water was added to stop the reaction. The precipitated products were subjected to the same sample separation, drying and analysis methods described in Example 4, showing the following results:
[0131] Horizontal control 1 - Solubility test. 20 mg of each of the obtained dry polyols were added to 2 mL of DMSO and completely dissolved, resulting in a translucent solution in all cases. This indicates that the polyurethane foam material has been depolymerized.
[0132] Level control 2-ATR-FTIR spectroscopy analysis (see Figure 7 Each of the obtained dry polyols was analyzed by ATR-FTIR, and its spectra (2-4) were compared with the spectrum (1) of the original polyurethane foam material. No characteristic bands of urethane bonds (1700-1740 cm -1 ): reaction medium [BmPyrr][Cl] + DBU + water (spectrum 2); reaction medium [BmPip][I] + DBU + water (spectrum 3); reaction medium [TBP][Br] + DBU + water (spectrum 4). This confirms the correct depolymerization of the polyurethane foam material according to the method of the present invention.
[0133] Level comparison 3-hydroxyl value determination. Since the hydroxyl values obtained for the different solid fractions are much higher than the hydroxyl values of the starting polyurethane foam material, the correct depolymerization according to these preferred embodiments of the process of the invention is again confirmed:
[0134] -PU standard: 9.45mg KOH / g polyol
[0135] - Reaction medium [BmPyrr][Cl] + DBU + water: 97.04 mg KOH / g polyol
[0136] - Reaction medium [BmPip][I] + DBU + water: 78.2 mg KOH / g polyol
[0137] - Reaction medium [TBP][Br] + DBU + water: 58.71 mg KOH / g polyol
[0138] Example 8 : PU foam was depolymerized at 95°C for 6 hours in a depolymerization reaction medium containing [Bmim][Ac], [Bmim][Cl], [Amim][Cl] or [TBP][Br] as an ionic liquid, TMG as a superbase and water as a nucleophile.
[0139] In four 50 mL screw-cap containers, 2 g of [Bmim][Ac], [Bmim][Cl], [Amim][Cl] or [TBP][Br] were added and mixed with 0.4 g of TMG, 0.6 g of water and 1 g of shredded polyurethane foam. The four containers were kept sealed and mechanically stirred at 95°C for 6 hours, and then 20 mL of water was added to stop the reaction. The precipitated products were subjected to the same sample separation, drying and analysis methods described in Example 4, showing the following results:
[0140] Horizontal control 1 - Solubility test. 20 mg of each of the obtained dry polyols were added to 2 mL of DMSO and completely dissolved, resulting in a translucent solution in all cases. This indicates that the polyurethane foam material has been depolymerized.
[0141] Level control 2-ATR-FTIR spectroscopy analysis (see Figure 8 Each of the obtained dry polyols was analyzed by ATR-FTIR, and its spectra (2-5) were compared with the spectrum (1) of the original polyurethane foam material. No characteristic bands of urethane bonds (1700-1740 cm -1 ): reaction medium [Bmim][Ac] + TMG + water (spectrum 2); reaction medium [Bmim][Cl] + TMG + water (spectrum 3); reaction medium [Amim][Cl] + TMG + water (spectrum 4); reaction medium [TBP][Br] + TMG + water (spectrum 5). This confirms the correct depolymerization of the polyurethane foam material according to the method of the present invention.
[0142] Level comparison 3-hydroxyl value determination. Since the hydroxyl values obtained for the different solid fractions are much higher than the hydroxyl values of the starting polyurethane foam material, the correct depolymerization according to these preferred embodiments of the process of the invention is again confirmed:
[0143] -PU standard: 9.45mg KOH / g polyol
[0144] - Reaction medium [Bmim][Ac] + TMG + water: 66.83 mg KOH / g polyol
[0145] - Reaction medium [Bmim][Cl] + TMG + water: 57.75 mg KOH / g polyol
[0146] - Reaction medium [Amim][Cl] + TMG + water: 67.43 mg KOH / g polyol
[0147] - Reaction medium [TBP][Br] + TMG + water: 58.56 mg KOH / g polyol
[0148] Example 9 : PU foam was depolymerized at 95°C for 6 hours in a depolymerization reaction medium containing [Bmim][Cl] as an ionic liquid, DBN as a superbase and water as a nucleophile.
[0149] 2 g of [Bmim][Cl] was added to a 50 mL screw cap container and mixed with 0.4 g of DBN, 0.6 g of water and 1 g of shredded polyurethane foam. The container was kept sealed and mechanically stirred at 95°C for 6 hours, and then 20 mL of water was added to stop the reaction. The precipitated product was subjected to the same sample separation, drying and analysis methods as described in Example 4, showing the following results:
[0150] Horizontal control 1 - Solubility test. 20 mg of the obtained dry polyol was added to 2 mL of DMSO and completely dissolved to obtain a translucent solution. This indicates that the polyurethane foam material has been depolymerized.
[0151] Level control 2-ATR-FTIR spectroscopy analysis (see Fig. 9 The obtained dry polyol was analyzed by ATR-FTIR and its spectrum (2) was compared with the spectrum (1) of the original polyurethane foam material. No characteristic bands of urethane bonds (1700-1740 cm -1 ), confirming the correct depolymerization of the polyurethane foam material according to the method of the present invention.
[0152] Level comparison 3-hydroxyl value determination. Since the hydroxyl value obtained for the solid fraction is much higher than that of the initial polyurethane foam material, the correct depolymerization according to this preferred embodiment of the process of the invention is again confirmed:
[0153] -PU standard: 9.45mg KOH / g polyol
[0154] -Reaction medium [Bmim][Cl] + DBN + water: 81.51 mg KOH / g polyol
[0155] Example 10: PU foam was depolymerized at 95°C for 6 hours in a depolymerization reaction medium containing [BmPyr][Cl] or [EPyr][Br] as an ionic liquid, DBU as a superbase and water as a nucleophile.
[0156] In two 50 mL screw-cap containers, 2 g of [BmPyr][Cl] or [Epyr][Br] was added and mixed with 0.4 g of DBU, 0.6 g of water and 1 g of ground polyurethane foam. The two containers were kept sealed and mechanically stirred at 95°C for 6 hours, and then 20 mL of water was added to stop the reaction. The precipitated product was subjected to the same sample separation, drying and analysis methods described in Example 4, showing the following results:
[0157] Horizontal control 1 - Solubility test. 20 mg of each of the obtained dry polyols were added to 2 mL of DMSO and completely dissolved, resulting in a translucent solution in all cases. This indicates that the polyurethane foam material has been depolymerized.
[0158] Level control 2-ATR-FTIR spectroscopy analysis (see Fig.10 Each of the obtained dry polyols was analyzed by ATR-FTIR, and its spectrum (2, 3) was compared with the spectrum (1) of the original polyurethane foam material. The characteristic bands of urethane bonds (1700-1740 cm -1 ): reaction medium [BmPyr][Cl]+DBU+water (spectrum 2); reaction medium [Epyr][Br]+DBU+water (spectrum 3). This confirms the correct depolymerization of the polyurethane foam material according to the process of the invention.
[0159] Level comparison 3-hydroxyl value determination. Since the hydroxyl values obtained for the different solid fractions are much higher than the hydroxyl values of the starting polyurethane foam material, the correct depolymerization according to these preferred embodiments of the process of the invention is again confirmed:
[0160] -PU standard: 9.45mg KOH / g polyol
[0161] - Reaction medium [BmPyr][Cl] + DBU + water: 66.28 mg KOH / g polyol
[0162] - Reaction medium [Epyr][Br] + DBU + water: 67.36 mg KOH / g polyol
[0163] Embodiment 11 : PU foam was depolymerized at 95°C for 6 hours in a depolymerization reaction medium containing [Bmim][Ac] as an ionic liquid, DBU as a superbase and methanol as a nucleophile.
[0164] 2 g of [Bmim][Ac] was added to a 50 mL screw cap container and mixed with 0.4 g of DBU, 0.6 g of methanol and 1 g of ground polyurethane foam. The container was kept sealed and mechanically stirred at 95°C for 6 hours, and then 20 mL of water was added to stop the reaction. The precipitated product was subjected to the same sample separation, drying and analysis methods described in Example 4, showing the following results:
[0165] Horizontal control 1 - Solubility test. 20 mg of the obtained dry polyol was added to 2 mL of DMSO and completely dissolved to obtain a translucent solution. This indicates that the polyurethane foam material has been depolymerized.
[0166] Level control 2-ATR-FTIR spectroscopy analysis (see Fig.11 The obtained dry polyol was analyzed by ATR-FTIR and its spectrum (2) was compared with the spectrum (1) of the original polyurethane foam material. No characteristic bands of urethane bonds (1700-1740 cm -1 ), confirming the correct depolymerization of the polyurethane foam material according to the method of the present invention.
[0167] Level comparison 3-hydroxyl value determination. Since the hydroxyl value obtained for the solid fraction is much higher than that of the initial polyurethane foam material, the correct depolymerization according to this preferred embodiment of the process of the invention is again confirmed:
[0168] -PU standard: 9.45mg KOH / g polyol
[0169] - Reaction medium [Bmim][Ac] + DBU + methanol: 62.06 mg KOH / g polyol
[0170] Example 12 : PU foam was depolymerized at 95°C for 6 hours in a depolymerization reaction medium containing [Bmim][Cl] or [BmPip][I] as an ionic liquid, TMG as a superbase and ethanol as a nucleophile.
[0171] In two 50 mL screw cap containers, 2 g of [Bmim][Cl] or [BmPip][I] was added and mixed with 0.4 g TMG, 0.6 g ethanol and 1 g of ground polyurethane foam. The two containers were kept sealed and mechanically stirred at 95 ° C for 6 hours, and then 20 mL of water was added to each container to stop the reaction. The precipitated product was subjected to the same sample separation, drying and analysis methods described in Example 4, showing the following results:
[0172] Horizontal control 1 - Solubility test. 20 mg of each of the obtained dry polyols were added to 2 mL of DMSO and completely dissolved, resulting in a translucent solution in all cases. This indicates that the polyurethane foam material has been depolymerized.
[0173] Level control 2-ATR-FTIR spectroscopy analysis (see Fig.11 Each of the obtained dry polyols was analyzed by ATR-FTIR, and its spectrum (3, 4) was compared with the spectrum (1) of the original polyurethane foam material. The characteristic bands of urethane bonds (1700-1740 cm -1 ): reaction medium [Bmim][Cl] + TMG + ethanol (spectrum 3); reaction medium [BmPip][I] + TMG + ethanol (spectrum 4). This confirms the correct depolymerization of the polyurethane foam material according to the process of the invention.
[0174] Level comparison 3-hydroxyl value determination. Since the hydroxyl values obtained for the different solid fractions are much higher than the hydroxyl values of the starting polyurethane foam material, the correct depolymerization according to these preferred embodiments of the process of the invention is again confirmed:
[0175] -PU standard: 9.45mg KOH / g polyol
[0176] -Reaction medium [Bmim][Cl] + TMG + ethanol: 61.23 mg KOH / g polyol
[0177] - Reaction medium [BmPip][I] + TMG + ethanol: 54.92 mg KOH / g polyol
[0178] Embodiment 13 : PU foam was depolymerized at 95°C for 6 hours in a depolymerization reaction medium containing 1-butylamine as a nucleophile, [Bmim][Cl] or [TBP][Br] as an ionic liquid, and DBU or DBN as a superbase.
[0179] 2 g of [Bmim][Cl] was added to a 50 mL screw cap container and mixed with 0.4 g of DBU. In a similar container, 2 g of [TBP][Br] and 0.4 g of DBN were added. Finally, 0.6 g of 1-butylamine and 1 g of ground polyurethane foam were added to each container, kept sealed and mechanically stirred at 95°C for 6 hours. 20 mL of water was then added to each container to stop the depolymerization reaction. The precipitated product was subjected to the same sample separation, drying and analysis methods described in Example 4, showing the following results:
[0180] Horizontal control 1 - Solubility test. 20 mg of each of the obtained dry polyols were added to 2 mL of DMSO and completely dissolved, resulting in a translucent solution in all cases. This indicates that the polyurethane foam material has been depolymerized.
[0181] Level control 2-ATR-FTIR spectroscopy analysis (see Fig.12 Each of the obtained dry polyols was analyzed by ATR-FTIR, and its spectrum (2, 3) was compared with the spectrum (1) of the original polyurethane foam. The characteristic bands of urethane bonds (1700-1740 cm -1 ): reaction medium [Bmim][Cl] + DBU + 1-butylamine (spectrum 2); reaction medium [TBP][Br] + DBN + 1-butylamine (spectrum 3). This confirms the correct depolymerization of the polyurethane according to the process of the invention.
[0182] Level comparison 3-hydroxyl value determination. Since the hydroxyl values obtained for the different solid fractions are much higher than the hydroxyl values of the starting polyurethane foam material, the correct depolymerization according to these preferred embodiments of the process of the invention is again confirmed:
[0183] -PU standard: 9.45mg KOH / g polyol
[0184] - Reaction medium [Bmim][Cl] + DBU + 1-butylamine: 90.04 mg KOH / g polyol
[0185] -Reaction medium [TBP] [Br] + DBN + 1-butylamine: 85.56 mg KOH / g polyol
[0186] Embodiment 14 : PU foam material was depolymerized at 95°C for 6 hours in a depolymerization reaction medium containing [Bmim][Cl], [BmPyrr][Cl], [BmPip][I], [BmPyr][Cl], [TBP][Br] or [EmPyr][Br] as ionic liquid, TBD as superbase and water as nucleophile.
[0187] In six 50 mL screw-cap containers, 2 g of [Bmim][Cl], [BmPyrr][Cl], [BmPip][I], [BmPyr][Cl], [TBP][Br] or [EmPyr][Br] were added respectively. Next, 0.4 g of TBD, 0.6 g of water and 1 g of ground polyurethane foam were added to each container, which was kept sealed and mechanically stirred at 95°C for 6 hours. 20 mL of water was then added to each container to stop the reaction. The precipitated products were subjected to the same sample separation, drying and analysis methods as described in Example 4, showing the following results:
[0188] Horizontal control 1 - Solubility test. 20 mg of each of the obtained dry polyols were added to 2 mL of DMSO and completely dissolved, giving a translucent solution in all cases.
[0189] Level control 2-ATR-FTIR spectroscopy analysis (see Fig.13 Each of the obtained dry polyols was analyzed by ATR-FTIR, and its spectra (2-7) were compared with the spectrum (1) of the original polyurethane foam material. No characteristic bands of urethane bonds (1700-1740 cm -1 ): reaction medium [Bmim][Cl] + TBD + water (spectrum 2); reaction medium [BmPyrr][Cl] + TBD + water (spectrum 3); reaction medium [BmPip][I] + TBD + water (spectrum 4); reaction medium [BmPyr][Cl] + TBD + water (spectrum 5); reaction medium [TBP][Br] + TBD + water (spectrum 6); reaction medium [EmPyr][Br] + TBD + water (spectrum 7). This confirms the correct depolymerization of the polyurethane foam material according to the method of the present invention.
[0190] Level comparison 3-hydroxyl value determination. Since the hydroxyl values obtained for the different solid fractions are much higher than the hydroxyl values of the starting polyurethane foam material, the correct depolymerization according to these preferred embodiments of the process of the invention is again confirmed:
[0191] -PU standard: 9.45mg KOH / g polyol
[0192] - Reaction medium [Bmim][Cl] + TBD + water: 96.61 mg KOH / g polyol
[0193] - Reaction medium [BmPyrr][Cl] + TBD + water: 79.66 mg KOH / g polyol
[0194] - Reaction medium [BmPip][I] + TBD + water: 111.46 mg KOH / g polyol
[0195] - Reaction medium [BmPyr][Cl] + TBD + water: 66.51 mg KOH / g polyol
[0196] - Reaction medium [TBP][Br] + TBD + water: 89.46 mg KOH / g polyol
[0197] - Reaction medium [EmPyr][Br] + TBD + water: 67.23 mg KOH / g polyol
[0198] Embodiment 15 : PU foam was depolymerized at 95°C for 6 hours in a depolymerization reaction medium containing [Bmim][Cl] or [BmPyrr][Cl] as an ionic liquid, TBD as a superbase and 1,2-isopropylidene glycerol (glycerol acetone acetal) as a nucleophile.
[0199] In two 50 mL screw-cap containers, 2 g of [Bmim][Cl] or [BmPyrr][Cl] was added. Next, 0.4 g of TMG, 0.6 g of acetone acetal and 1 g of chopped polyurethane foam were added to each container, kept sealed and mechanically stirred at 95 ° C for 6 hours. Then, 20 mL of water was added to each container to stop the reaction. The precipitated product was subjected to the same sample separation, drying and analysis methods described in Example 4, showing the following results:
[0200] Horizontal control 1 - Solubility test. 20 mg of each of the obtained dry polyols were added to 2 mL of DMSO and completely dissolved, resulting in a translucent solution in all cases. This indicates that the polyurethane foam material has been depolymerized.
[0201] Level control 2-ATR-FTIR spectroscopy analysis (see Fig.14 Each of the obtained dry polyols was analyzed by ATR-FTIR, and its spectrum (2, 3) was compared with the spectrum (1) of the original polyurethane foam material. The characteristic bands of urethane bonds (1700-1740 cm -1 ): reaction medium [Bmim][Cl] + TBD + acetone acetal (spectrum 2); reaction medium [BmPyrr][Cl] + TBD + acetone acetal (spectrum 3). This confirms the correct depolymerization of the polyurethane foam material according to the process of the invention.
[0202] Level comparison 3-hydroxyl value determination. Since the hydroxyl values obtained for the different solid fractions are much higher than the hydroxyl values of the starting polyurethane foam material, the correct depolymerization according to these preferred embodiments of the process of the invention is again confirmed:
[0203] -PU standard: 9.45mg KOH / g polyol
[0204] - Reaction medium [Bmim][Cl] + TBD + acetone glycerol: 117.19 mg KOH / g polyol
[0205] - Reaction medium [BmPyrr][Cl] + TBD + acetone glycerol: 65.71 mg KOH / g polyol
[0206] Example 16: Cleavage of the carbamate bond of oxybis(2,1-ethylenediyl)bis(phenylcarbamate) substances in a reaction medium containing [Bmim][Cl] as an ionic liquid, DBU, TBD, pyrrolidine, tert-butylamine or triethylamine as a basic catalyst, and water as a nucleophile.
[0207] In five 50 mL screw-cap containers, add 1.334 g [Bmim] [Cl]. Next, add the corresponding superbase to each container: 0.267 g DBU (pK a =13.5); 0.249 g TBD (pK a =15.2); 0.148 g pyrrolidine (pK a =11.3); 0.189 g tert-butylamine (pK a =10.7); or 0.251 g triethylamine (pK a =10.8). Finally, 0.4 g of water and 0.05 g of oxybis(2,1-ethylenediyl)bis(phenylcarbamate) were added, and the container was kept sealed and mechanically stirred at 95°C for 4 hours. Then, 10 mL of chloroform and 10 mL of water were added to the reaction mixture. The phases were separated and the organic phase was washed with water (2×10 mL). Finally, the organic phase was collected, dried over anhydrous MgSO4, and the solvent was evaporated in a rotary evaporator. The ATR-FTIR ( Fig.15a ) and HPLC( Fig.15b )Analyze the obtained product.
[0208] from Fig.15a It can be observed in spectra 2 and 3 that in the reaction carried out in the presence of ionic liquid, superbase and nucleophile, the -1 The absence of a band at 100° confirmed the complete disappearance of the carbonyl group corresponding to the carbamate bond. a The band still exists when less than 12 bases are bound (see Fig.15a 4, 5 and 6). These results were also confirmed in the HPLC chromatograms ( Fig.15b ), where the peak corresponding to the carbamate bond disappears in favor of the peak associated with carbamate cleavage, and other new peaks appear that are associated with the ions formed between the superbase (either DBU or TBD) and the hydrolysis product (see Fig.15b Medium Spectrum Figure 2 and 3 Comparative color spectrum Figure 4-6 ).
[0209] Embodiment 17: Separation and characterization of the products isolated after cleavage of the carbamate bond of oxybis(di(ethane-2,1-ethylenediyl)bis(phenylcarbamate) species in a reaction medium containing [Bmim][Cl] as an ionic liquid, DBU as a superbase and water as a nucleophile.
[0210] After completing the depolymerization reaction described in Example 16 (wherein a reaction medium consisting of [Bmim][Cl], DBU and water was used), the main product obtained was separated by chromatography using silica gel as the stationary phase and a dichloromethane / methanol mixture as the mobile phase (ratios varied from 100 / 0 to 95 / 15 v / v). The pure product was analyzed as follows:
[0211] 1 H-RMN (300MHz, CDCl3): δ7.88(s,2H)|7.34(dt,J=8.8,1.7Hz,4H)|7.25–7.15(m,4H)|7.00–6.83(m,2H)|6.16(t,J=5.9 Hz,2H)|3.37(t,J=6.7Hz,4H)|3.24(dd,J=10.3,6.0Hz,4H)|3.21–3.08(m,5H)|2.56–2.37(m,4H)|1.77–1.47(m,16H)(see Fig.16 A);
[0212] 13 C-RMN (101MHz, CDCl3): δ176.64|156.28|139.74|128.86|122.26|119.26|49.67|45.65|37.18|36.88|29.83|28.38|28.21|23.32 (see Fig.16 B);
[0213] ATR-FTIR: ν(cm -1 )=3337|3336|3331|2930|1690|1613|1597|1548|1497|1440|
[0214] 1368|1353|1310|1227|1199|1176|1153|1112|1081|1031|978|909|853|753|726|693|644(See Fig.16 C), and
[0215] Mass spectrum: m / z: [M+Na] + [C 16 H 23 N3O2Na] +Calculated value = 312.1689; measured value: 312.1686.
[0216] Embodiment 18 : HPLC method for monitoring the conversion of carbamate groups during carbamate bond cleavage of oxybis(2,1-ethanediyl)bis(phenylcarbamate).
[0217] The HPLC-DAD method used the following conditions: 100 mm long C-18 column, flow rate 0.5 mL / min, initial pressure 43-44 bar, column temperature 30°C, detector temperature 50°C, sample volume 10 μL, wavelength 220 nm, time 30 minutes, gradient acetonitrile (ACN)-water (0-5 minutes 5% ACN, 5-8 minutes 5%-20% ACN, 8-13 minutes 20%-60% ACN, 13-18 minutes 60%-95% ACN, 18-23 minutes hold 95% ACN, then from 23-25 minutes from 95% ACN to 5% ACN, and from 25-30 minutes hold 5% ACN). Under these conditions, the presence of the carbamate model oxybis(2,1-ethanediyl)bis(phenylcarbamate) was identified by the appearance of a signal at a retention time of 18.12 minutes (see Fig.17b Chromatogram A).
[0218] Sampling of the products analyzed in the different reactions with the carbamate model oxybis(2,1-ethanediyl)bis(phenylcarbamate) consisted of dissolving all of the obtained product (according to the method described in Example 16) in 3 mL of MeOH, then taking out a 50 μL aliquot of the solution and diluting it in 1 mL of MeOH.
[0219] Embodiment 19 : Cleavage of the carbamate bond of oxybis(2,1-ethylenediyl)bis(phenylcarbamate) species in a depolymerization reaction medium containing [Bmim][Cl] as an ionic liquid, different amounts of DBU as a superbase, and water as a nucleophile.
[0220] 1.334 g of [Bmim][Cl] was added to three 50 mL screw cap containers. Next, the corresponding amount of DBU (0.267 g for the 12.3 equivalent study, 0.108 g for the 5 equivalent study, and 0 g for the study without DBU), 0.4 g of water, and 0.05 g of oxybis(2,1-ethylenediyl)bis(phenylcarbamate) were added to each container, which was kept sealed and mechanically stirred at 95° C. for 4 hours. It was then subjected to the same isolation and drying methods described in Example 16.
[0221] In each case, by 1 H-NMR( Fig.17a ) and HPLC( Fig.17b ) was used to analyze the products isolated after the cleavage of the carbamate bond of oxybis(2,1-ethylenediyl)bis(phenylcarbamate). The results obtained once again demonstrated that in the absence of one of the elements (superbase) in the reaction mixture, the carbamate bond was not cleaved ( Fig.17a and 17b Compare spectrum E in Figure 1 with C and D), recovering the intact starting carbamate.
[0222] Embodiment 20 : PU foam material was depolymerized at 95°C for 6 hours in a depolymerization reaction medium containing [Bmim][Cl] as an ionic liquid, DBU, TBD, pyrrolidine, tert-butylamine or triethylamine as a basic catalyst, and water as a nucleophile.
[0223] 2g [Bmim] [Cl] was added to five 50mL screw cap containers. Next, 0.4g of the corresponding basic catalyst (DBU, TBD, pyrrolidine, tert-butylamine or triethylamine), 0.6g of water and 1g of ground polyurethane foam were added to each container, which was kept airtight and mechanically stirred at 95°C for 6 hours. Then, 20mL of water was added to each container to stop the reaction. The precipitated product was subjected to the same sample separation, drying and analytical method as described in Example 3, showing the following results:
[0224] Horizontal control 1 - Solubility test. 20 mg of dry polyol obtained using superbase DBU or superbase TBD as alkaline catalyst was added to 2 mL DMSO and completely dissolved to obtain a translucent solution. In contrast, for products obtained using a base (i.e., pyrrolidine, tert-butylamine or triethylamine) as alkaline catalyst, 20 mg of the product was added to 2 mL DMSO to produce an insoluble precipitate.
[0225] Level control 2-ATR-FTIR spectroscopy analysis (see Fig.18 Each of the obtained dry polyols was analyzed by ATR-FTIR and its spectra (2-6) were compared with the spectrum of the original polyurethane foam material (spectrum 1). In the case of using DBU (spectrum 2) or TBD (spectrum 3) as superbase, no characteristic bands of urethane bonds (1700-1740 cm -1 ), but this characteristic band was observed when pyrrolidine (spectrum 4), tert-butylamine (spectrum 5) or triethylamine (spectrum 6) was used.
[0226] These results confirm the same reaction observed in Example 16. Only the use of a reaction medium consisting of a combination of an ionic liquid, a superbase, and a nucleophile results in cleavage of the urethane bonds and, therefore, depolymerization of the polyurethane species at temperatures below 100°C.
[0227] Embodiment 21 : In a reaction medium containing [Bmim][Cl], [Bmim][AcO], [TBP][Br] or [BmPyr][Cl] as an ionic liquid, DBU as a superbase, and water as a nucleophile, the carbamate bond of the oxybis(2,1-ethylenediyl)bis(phenylcarbamate) substance is cleaved.
[0228] In four 50 mL screw-cap containers, 1.334 g [Bmim] [Cl], 1.666 g [Bmim] [AcO], 2.5917 g [TBP] [Br] or 1.4183 g [BmPyr] [Cl] were added respectively. Next, 0.267 g DBU, 0.4 g water and 0.05 g carbamate model oxybis (2,1-ethylenediyl) bis (phenylcarbamate) were added to each container, kept sealed and mechanically stirred at 95 ° C for 4 hours. Then, it was subjected to the same separation and drying method described in Example 16. The obtained product was analyzed by HPLC (see Fig.19 ).
[0229] This embodiment again illustrates the need for a reaction medium consisting of an ionic liquid, a superbase and a nucleophile to achieve cleavage of the carbamate bond. Regardless of the type of ionic liquid used, the complete disappearance of the peak associated with the carbamate bond demonstrates the efficiency of the cleavage.
Claims
1. A method for depolymerizing a polyurethane material, wherein the method comprises performing the following steps: a) mixing the polyurethane material with a depolymerization reaction medium, wherein the depolymerization reaction medium comprises an ionic liquid, a basic catalyst and a nucleophile; and b) obtaining two mutually immiscible fractions from the mixture obtained in step a): A first fraction comprising at least one polyol material; and a second fraction comprising at least the ionic liquid and the basic catalyst; The method is characterized in that: The depolymerization reaction medium comprises: an ionic liquid in a proportion greater than or equal to 50% w / w relative to the total weight of the depolymerization reaction medium; Superbases, as alkaline catalysts; and a nucleophile in a proportion less than or equal to 15% w / w relative to the total weight of the depolymerization reaction medium; Step a) is carried out at a temperature of 50-100° C. for 2 minutes to 10 hours; and Step b) comprises performing the following sub-steps: i. adding to the mixture of step a) 4 to 40 times the weight of the depolymerization reaction medium proton molecule solvent; ii. placing the mixture of step i) at a temperature of 20-60°C for at least 1 hour; and iii. Separate the obtained fractions.
2. A method according to the preceding claim, wherein the polyurethane substance comprises a thermosetting polyurethane.
3. The method of the preceding claim, wherein the thermoset polyurethane comprises a polyurethane foam.
4. The process according to any one of the preceding claims, wherein in step a), the polyurethane material is mixed with the depolymerization reaction medium in a mass ratio of 1:20 to 1:
1.
5. The process according to the preceding claim, wherein in step a), the polyurethane substance is mixed with the depolymerization reaction medium in a mass ratio of 1:15 to 1:
3.
6. The process according to the preceding claim, wherein in step a), the polyurethane substance is mixed with the depolymerization reaction medium in a mass ratio of 1:10 to 1:
5.
7. The process according to any one of the preceding claims, wherein step a) is carried out at a temperature of 80-100°C and / or for a period of 2 to 8 hours.
8. The process according to the preceding claim, wherein step a) is carried out at a temperature of 90-98°C and / or for a period of 3 to 7 hours.
9. The process according to any one of the preceding claims, wherein step a) is carried out in a depolymerization reaction medium comprising the ionic liquid in a proportion ranging from 50% w / w to 85% w / w relative to the total weight of the depolymerization reaction medium.
10. The process according to the preceding claim, wherein the depolymerization reaction medium comprises an ionic liquid in a proportion ranging from 65% w / w to 80% w / w relative to the total weight of the depolymerization reaction medium.
11. The process according to any one of the preceding claims, wherein step a) is carried out in a depolymerization reaction medium comprising a proportion of 1% w / w to 15% w / w of nucleophile relative to the total weight of the depolymerization reaction medium.
12. The process according to the preceding claim, wherein the depolymerization reaction medium comprises a nucleophile in a proportion ranging from 5% w / w to 15% w / w relative to the total weight of the depolymerization reaction medium.
13. The process according to any one of the preceding claims, wherein in step b), the amount of protic molecular solvent added is 5 to 15 times the weight of the depolymerization reaction medium.
14. The method according to any one of the preceding claims, wherein step a) is performed with a nucleophile comprising water, an alcohol, an amine, or any possible combination thereof.
15. A method according to the preceding claim, wherein the nucleophile comprises at least 80% water.
16. The method according to any one of the preceding claims, wherein sub-step i) is performed with a protic molecular solvent comprising water, methanol, ethanol, isopropanol, or any possible combination thereof.
17. The method according to the preceding claim, wherein the protic molecular solvent comprises at least 80% water.
18. The method according to any one of the preceding claims, wherein step a) is performed with an ionic liquid comprising: a cation selected from dialkyl imidazoles, tetraalkyl ammoniums, dialkyl piperidines, alkyl pyridines, dialkyl pyrrolidines and / or tetraalkyl phosphines, and / or Anions are selected from fluoride, chloride, bromide, iodide, acetate, trifluoroacetate, formate and / or carbonate.
19. The method of claim 1, wherein the ionic liquid comprises 1-butyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium acetate, 1-butyl-3-methylpyridinium chloride, 1-butyl-3-methylpyridinium bromide, 1-butyl-3-methylpyridinium iodide, 1-butyl-1-methylpiperidinium chloride, 1-butyl-1-methylpiperidinium bromide, 1-butyl-1-methylpiperidinium iodide, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium bromide, 1-butyl-3-methylimidazolium iodide, 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium iodide, 1-butyl-4-methylpyridinium chloride, 1-butyl-3-methylimidazolium formate, 1-hexyl-3-methylimidazole chloride, 1-hexyl-3-methylimidazole bromide, 1-hexyl-3-methylimidazole iodide, 1-octyl-3-methylimidazole chloride, 1-octyl-3-methylimidazole bromide, 1-octyl-3-methylimidazole iodide, 1-allyl-3-methylimidazole chloride, 1-butyl-3-methylimidazole acetate, 1-butyl-3-methylimidazole bromide, 1-ethyl-2-methylpyridine bromide, N-ethylpyridine bromide, 1-butyl-3-methylimidazole chloride, 1-butyl-1-methylpyrrole chloride, 1-butyl-1-methylpiperidinium iodide, tetrabutylphosphine bromide, tetrabutylphosphine chloride, 1-butyl-2-methylpyridine chloride, 1-ethyl-1-methyl-piperidinium chloride, or any possible combination thereof.
20. The method according to any one of the preceding claims, wherein the superbase comprises at least a bicyclic amidine, a bicyclic amidine derivative, a guanidine, a guanidine derivative, or any possible combination thereof.
21. The method according to the preceding claim, wherein the superbase comprises 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,5-diazabicyclo[4.3.0]non-5-ene (DBN), 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD), tetramethylguanidine (TMG), or any possible combination thereof.
22. The method according to any one of the preceding claims, comprising at least one of the following additional steps: reusing the first fraction in the synthesis of new polyurethane; and / or The second fraction is reused in step a) of the novel process for depolymerizing polyurethane substances.
23. A method according to any one of the preceding claims, further comprising a drying step of drying the first fraction and / or the second fraction to a value which reduces the water content of the fraction to less than 1% w / w.
24. The method according to the preceding claim, wherein the drying step comprises freeze drying, vacuum evaporation, heating, distillation, resin adsorption, or any possible combination thereof.
25. A method according to claims 22-24, comprising a preceding step of treating the second fraction with a hydrophobic adsorbent.
26. A method according to the preceding claim, wherein the hydrophobic absorbent comprises activated carbon or polystyrene resin.
27. The method according to any one of the preceding claims, wherein sub-step iii) comprises a process of centrifugation, decantation, filtration, vacuum filtration, resin adsorption, or any possible combination thereof.
28. A method according to any preceding claim, comprising the additional step of verifying the progress and completion of steps a) and / or b).
Citation Information
Patent Citations
Hydrolysis of polyurethanes
EP0011662B1
Process for the recovery of polyols from polyurethane foam waste using a novel catalyst
EP1693409A1
Production method of regenerated polyol
JP2003064218A
Catalytic depolymerization of polymers containing electrophilic linkages using nucleophilic reagents
US20040127720A1
Hydrolysis of polyurethanes
US5208379A
Cited By
Method for preparing polyol by catalyzing degradation of waste polyurethane by using attapulgite / ZIF-8 composite material
CN121343242A
Method for depolymerizing polyurethane based on diester carbonate under catalysis of halogen salt substances
CN121405587A